Student's perspective: Mathematical reasoning ability and correlations between mathematics and physics - Hamdi, Muhammad Najih; Handayani, Rif’ati Dina; Supriadi, Bambang (Journal of Environment and Sustainability Education, 2024)
The purpose of this study is to understand students' perspectives on the process of solving physics problems using the mathematical reasoning approach during physics learning that has been passed. This study used qualitative methods with data condensation analysis, data collection through semi-structured interviews. Participants were 36 students from a high school in Jember, East Java. Obtained themes and sub-themes in accordance with the research objectives and the list of questions that have been made, namely: (1) mathematical reasoning ability-presenting conjectures, predicting answers and the solution process, mathematical manipulation, drawing conclusions, and (2) the correlations between mathematics and physics-mathematics and physics, examples of mathematical applications in physics. Students need to develop mathematical reasoning skills and an understanding of the relationship between mathematics and physics.